Da'wah and the Dynamics of Modern Communication - Muhammad Thahir (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This article discusses the adaptation of da'wah strategies in modern communication dynamics, The method and approach used in this study is library research with a descriptive qualitative approach through literature study, content analysis, and meta-analysis, to obtain a comprehensive understanding. Based on the study in this paper, it is found that da'wah needs to be adapted to the development of modern communication. Social media platforms become very important as one of the effective media in da'wah by referring to ethical/moral values and professionalism while still paying attention to the social and cultural context to maintain quality and harmonious communication with all parties.